Risk Management in Deep Excavation - Tabar, Mehrdad Rashidi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Urban decision-makers such as private owners or public section (e.g. municipality) are encouraged to optimize the use of land in underground which has opportunity of economic or social benefits such as Metro stations, multi-story commercial buildings with parking lots or shops in underground. These decisions can be endangered in construction processes. There are few scientific and formal reports about irrecoverable damages, fatalities and geotechnical engineering researches to predict side soil displacements, strength, and their allowable quantities to reach an improved design technique for retaining supports and soil stability. But construction processes may face possible risks such as geotechnical, structural and productivity risks which have additional cost and increased duration. Therefore, risk management in deep excavation is a crucial field to study and there isn‘t any collective scientific resource on that subject. This thesis have prepared a collective resource from related scientific fields, summary of case studies, and case histories in deep excavation to be use in risk management. The objectives are geotechnical, structural, and construction productive risk identification, risk occurrence probability, and risk consequence that are the parameters of risk assessment, which is require for risk response plan in risk management. In this manner, construction methods and equipment in deep excavation are summarized and classified by a proposed facade vision. A deterministic method is proposed for geotechnical risk occurrence probability estimation based on factor of safety concept. A method is proposed for classifying deep excavation damages and estimating expected internal, external, and accidental damages as a consequence in deep excavation is proposed. In order to identifying risks, site investigation and underground identification is overviewed and a model based on range of parameters for classification and identification of clays, granular soils, and intermediate soils is developed which are required for sensitivity analysis as a method of risk assessment. For risk identification and analysis, different geotechnical failure modes, structural failures and their effects on adjacent land and building such as settlement, cracks, is overviewed and collected. The repair state classification and dewatering effects are overviewed, and collected as well. Method of estimating expected internal, external, and accidental induced-damages in deep excavation is proposed and compared in each stage. Also risks and uncertainties in productivity such as production rate, work duration, and unit cost is discussed for considering the preparation of response plan in construction of deep excavation. Geotechnical risk occurrence probability estimation and risk consequences in deep excavation are innovative proposed method. Site geotechnical investigation and identification for risk management in deep excavation is innovative expanded method. Cost risk management in deep excavation is innovative expanded method.

ÖZ: Őzel sectőr veya kamu yőnetimleri (őr: belediyeler) gibi kentsel karar vericiler, Metro istasyonlari, yeraltinda dűkkan ve otopark alanli ticari binalar yapimi, economic ve sosyal fayda firsatlari vermesi bakimindan yeralti alanlarinin optimizasyonu teşfik edilir. Bu kararlar inşaat işlemlerinde tehlikeye yol açabilir. Istinat desteklenmesi ve sabitlemesi için gelişmiş tasarim tekniklerine ulaşmak için, toprak deplasmani, mukavemeti ve onlarin kabuledilebilir miktarlarini tahmin etmekte kullanilaçak, telafisi olmayan hasarlar, őlűmler ve geoteknik műhendisliġi çalişmasi hakkinda az sayinda bilimsel ve resmi rapor var. Fakat inşaat işlemleri, ek maliyet ve uzatilmiş inşaat sűresi gibi sorunçlar doğurabilecek, geoteknik sel, yapisal ve verimlilik riskleri gibi bazi olasi risklerle karşilașir. Bu yűzden, derin kazilardaki risk yőnetimi çok őnemli bir çalișma olanidir ve bu konuda toplu bir bilimsel kaynak yoktur. Bu tezle, risk yonetiminde kullanilmak űzere derin kazilar ile ilgili bilimsel alanlardan, őrnek çalișmalardan ve őrnek geçmiş olay kayitlarindan faydalanilarak bir toplu kaynak hazirlanmiştir. Amaç, risk yőnetimi için, geotekniksel, yapisal ve verimlilik risk tanimlamasi, ve risk degerlendirmesini oluşturan, risk oluşma olasiliği ve sonucu parameterlerini hazirlamaktir. Bőylelikle, derinkazilardaki anşaat methodlari ve ekipmanlari bir őnerilmiş cephe vizyonuyla őzetlenmiş ve siniflandirilmiş oldu. Emniyet faktorű koseptine dayanarak, geotekniksel risk oluşma olasiliği için bir deterministic method őnerildi. Derin kazi sonucu olarak, derin kazi hasarlari siniflandirmasi ve beklenen içsel, dişsal ve kaza neticesi olan hasarlar için bir method őnerildi. Bir risk değermelendis metodu olarak duyarlilik analizi için gerekli olan risk tanimlamasi için, saha incelemesi ve yeralti tanimlamasi gőzden geçirildi ve kil, granul toprak ve orta topraklar siniflandirmasi ve tanimlamasi için parameter araliklarina bağli olarak bir model geliştirildi. Risk tanimlamasi ve analizi için farkli geoteknik başarisizlik modelari, yapisal başarisizlik ve onlarin komşu arazi ve binalar űzerindeki oturma, çatlama gibi etkileri gőzdan geçirildi ve toplandi. Onarim durumu siniflandirmasi ve su tahliye etkileride gőzdan geçirildi ve toplandi. Derin kazilardaki, beklenen içsel, dişsal ve kaza sebepli hasar tahmini metodu őnerildi ve her seviyede karşilaştirildi. Derin kazi inşaasi müdahale plani hazirlanmasi gőz őnünde tutularak, üretim hizi, iş sűresi ve birim maliyet gibi verimlilik konusundaki riskler ve belirsizlikler de tartişilmiştir. Derin kazı jeoteknik risk oluşumu olasılığı tahmini ve risk sonuçları yenilikçi önerilen yöntemdir. Derin kazı risk yönetimi için site jeoteknik araştırma ve kimlik yenilikçi genişletilmiş bir yöntemdir. Derin kazı Maliyet risk yönetimi, yenilikçi genişletilmiş bir yöntemdir.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Dr. Tolga Çelik.
Keywords: Underground construction--Soil mechanics; Deep excavation; risk occurrence probability; risk consequence; geotechnical risk; Cost and duration risk; production rate risk; risk response plan; Civil Engineering